2006
DOI: 10.1038/sj.onc.1209576
|View full text |Cite
|
Sign up to set email alerts
|

Human glutathione S-transferase P1-1 interacts with TRAF2 and regulates TRAF2–ASK1 signals

Abstract: Human glutathione S-transferase P1-1 (GSTP1-1) is an ubiquitously expressed protein that plays an important role in the detoxification and xenobiotics metabolism. It has been shown that GSTP1-1 interacts with c-Jun NH 2 -terminal kinase (JNK) and suppresses its activity. Here, we report a novel function of GSTP1-1 in regulating tumor necrosis factor-a (TNF-a)-triggered signaling. The present experiments showed that GSTP1-1 physically associated with tumor necrosis factor receptor-associated factor 2 (TRAF2) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(163 citation statements)
references
References 67 publications
7
151
0
Order By: Relevance
“…We suggest that GST pi predominantly utilizes a different interface for other protein-protein interactions that is distinguishable from the homodimeric interface. GST pi appears to form complexes with other proteins such as Jun N-terminal kinase [30][31][32] and tumor necrosis factor alpha [33]. If the other proteins interact entirely with the same site of GST pi occupied by 1-Cys Prx, complexes with these proteins seem likely to form with a GST monomer.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that GST pi predominantly utilizes a different interface for other protein-protein interactions that is distinguishable from the homodimeric interface. GST pi appears to form complexes with other proteins such as Jun N-terminal kinase [30][31][32] and tumor necrosis factor alpha [33]. If the other proteins interact entirely with the same site of GST pi occupied by 1-Cys Prx, complexes with these proteins seem likely to form with a GST monomer.…”
Section: Discussionmentioning
confidence: 99%
“…The NBD derivatives 1e40 were obtained by nucleophilic displacement reactions between the commercially available 4-chloro-7-nitrobenzo[c] [1,2,5] The not commercially available thiols were obtained by the reactions reported in Schemes 2e6. The thiophenols 41 and 43e50 were obtained by simultaneous acid activation/thiol protection of the commercial 4-mercaptobenzoic or 3-(4-mercaptophenyl)propionic acids with ethyl chloroformate in dimethoxyethane in the presence of N-methylmorpholine at room temperature, followed first by coupling with an appropriate amine and then by thiol deprotection with sodium methoxide in dry MeOH at room temperature.…”
Section: Chemistrymentioning
confidence: 99%
“…In fact, Adler et al 2 had demonstrated that GSTP1-1 efficiently inhibits the activity of JNK by forming a GSTP1-1 : JNK heterocomplex. Furthermore, Wu et al 3 have recently shown that GSTP1-1 inhibits TRAF2 in human cervical carcinoma HeLa cells. TRAF2 is an adaptor protein which mediates the signal transduction of different receptors 4 and it is required for the activation of the apoptosis signal-regulating kinase (ASK1), which in turn activates both mitogen-activated protein kinase (MKK)4/7-JNK and MKK3/4/6-p38 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%